Perancangan Video Dokumenter Redesign Sortali dalam Budaya Batak Toba sebagai Upaya Pelestarian Estetika Tradisional bagi Generasi Muda Masa Kini - Togu Hutabarat (Misterius : Publikasi Ilmu Seni dan Desain Komunikasi Visual., 2025)
The existence of a new design of this sortali is able to provide satisfaction to users in Batak Toba cultural events themselves. This writing aims to tell an interesting design in the more modern development of sortali. The design results in the form of a documentary video that provides information related to the existence of a new design on sortali that is ready to be used for major Batak Toba cultural events, especially weddings. The new design of sortali in Batak Toba culture brings fresh perspectives to the traditional accessory, which has long been a symbol of cultural pride and identity. The updated design not only maintains the core values of Batak Toba craftsmanship but also integrates modern touches that cater to the preferences of today’s younger generation. This innovative approach is expected to meet the demands of Batak Toba cultural events, where authenticity and tradition are highly valued, while also introducing a more contemporary aesthetic that appeals to a wider audience. The documentary video serves as an informative tool to highlight this evolution in sortali design. Through engaging visuals and interviews with local artisans and cultural experts, the video offers an in-depth look at the process of redesigning this iconic piece of cultural attire. It sheds light on the challenges and successes of merging tradition with modernity, demonstrating how the new design respects Batak Toba heritage while embracing innovation. By featuring real-life applications of the redesigned sortali in major cultural events, especially weddings, the video illustrates its functionality and versatility in contemporary settings. Moreover, the design of the new sortali is not just about aesthetics; it is also a statement about preserving cultural heritage in the face of modernization.